ChemInform Abstract: Asymmetric Total Synthesis of Novel Pentacyclic Indole Alkaloid, Kopsiyunnanine E, Isolated from Kopsia Arborea. Issue 14 (April 2015) - Kitajima, Mariko; Murakami, Yosuke; Takahashi, Nobuaki; Wu, Yuqiu; Kogure, Noriyuki; Zhang, Rong‐Ping; Takayama, Hiromitsu
Abstract: The first asymmetric total synthesis of kopsiyunnanine E is described.